RfiA, a novel PAP2 domain-containing polytopic membrane protein that confers resistance to the FtsZ inhibitor PC190723. (March 2015) - Chen, Ximing; Zhang, Binglin; Xiao, Jianxi; Ju, Furong; Li, Shuyan; Ren, Cuiling; An, Lizhe; Chen, Tuo; Liu, Guangxiu; Facey, Paul; Mullins, Jonathan GL; Dyson, Paul
ABSTRACT : Background: As an essential protein for bacterial cell division, the tubulin-like FtsZ protein has been selected as a target for development of next generation antimicrobials. PC190723 is a fluoride-containing benzamide compound developed as a FtsZ inhibitor that selectively inhibits growth of multidrug resistant Gram-positive bacteria.Aim: Our aim was to investigate the mechanism of resistance to PC109723 conferred by over-expression of a gene, rfiA, in an environmental bacterium Arthrobacter A3.Materials & methods: The investigations included analysis of the effect of PC109723 on wild-type Arthrobacter A3 and a recombinant strain over-expressing rfiA, in vivo localization of RfiA, in vitro measurements of fluorine release from PC109723 by membrane extracts from the over-expression strain combined with mass spectrophotometric analysis of reaction products, and modelling of RfiA structure.Results: We describe a novel protein, RfiA, from Arthrobacter A3 that confers PC190723 resistance. RfiA is a PAP2 domain-containing polytopic transmembrane protein that can modify the fluoridated benzamide ring that is critical for high affinity binding of PC190723 with FtsZ.Conclusion: RfiA-mediated modification of PC190723 is the first reported instance of resistance to this antibiotic involving a change to its structure. We predict that adoption of PC190723 or related benzamides as antimicrobials in clinical practice will lead to the acquisition by resistant pathogens of a gene encoding this subfamily of proteins